2018
DOI: 10.1097/md.0000000000013200
|View full text |Cite
|
Sign up to set email alerts
|

CT diagnosis for metastasis of clear cell renal cell carcinoma to the pancreas

Abstract: Rationale:Clear cell renal cell carcinoma (CCRCC) metastasis to pancreas is clinically rare. Misdiagnosis for these cases is frequently due to the low incidence, lack of specific clinical symptoms, and laboratory results.Patient concerns:Three female patients aged 47 years, 69 years, and 76 years, respectively, were admitted to hospital for routine examination after resection of clear cell carcinoma of kidney for 69 months, 57 months, and 123 months, respectively. All 3 cases had no specific clinical symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Most metastases in the pancreas are discovered as a part of widespread systemic disease at the time of diagnosis[ 22 ]. Renal cell carcinoma, colorectal cancer, melanoma, and lung cancer are the most frequent primary malignancies that cause pancreatic metastases; pancreatic metastases from synovial soft tissue sarcoma are extremely uncommon[ 23 - 26 ]. A review of pancreatic metastases of sarcomas other than clear cell sarcoma showed that the primary tumor was located in the lower limbs[ 27 ].…”
Section: Metastatic Clear Cell Sarcoma In the Pancreasmentioning
confidence: 99%
“…Most metastases in the pancreas are discovered as a part of widespread systemic disease at the time of diagnosis[ 22 ]. Renal cell carcinoma, colorectal cancer, melanoma, and lung cancer are the most frequent primary malignancies that cause pancreatic metastases; pancreatic metastases from synovial soft tissue sarcoma are extremely uncommon[ 23 - 26 ]. A review of pancreatic metastases of sarcomas other than clear cell sarcoma showed that the primary tumor was located in the lower limbs[ 27 ].…”
Section: Metastatic Clear Cell Sarcoma In the Pancreasmentioning
confidence: 99%
“… 1 , 4 , 5 Pancreatic metastases are uncommon, seen in only two to five percent of all malignancies including RCC, melanomas, colorectal carcinomas, breast cancers, and sarcomas. 6 , 7 RCC is the most common primary tumor leading to pancreatic metastases, with pancreatic metastases found in three to ten percent of metastatic RCC cases. 8 …”
Section: Introductionmentioning
confidence: 99%
“…9 The current literature on oligometastatic RCC pancreas tumors is comprised of individual case studies and small retrospective reviews, with most reviews looking at the utility of pancreatectomy as an option for disease management. 6 , 9 , 10 , 11 For isolated pancreas metastases, a partial or total pancreatectomy may be a feasible option for patients that are appropriate surgical candidates. Given that this can be a highly morbid surgery and some data demonstrates no clear OS benefit with surgery versus systemic therapy, there is interest in determining the role of non-surgical treatment options for patients with pancreatic oligometastatic disease.…”
Section: Introductionmentioning
confidence: 99%